Implementasi Ajaran Catur Marga Yoga dalam Kehidupan Masyarakat Hindu - – Evie (Fakultas Dharma Duta, 2019)
Catur Marga are the four ways or manners of the members of a religious community of Hindu for honor and go in the direction of way the God or Ida Sang Hyang Widhi Wasa. The source of teaching Catur Marga are teach in purified literature Bhagawadgita, the main of Trayodhyaya about Karma Marga Yoga, that is one system which content the teaching that the different of teach Subha Karma (good action) with the teach of Asubha Karma (not good action). Karma has two kinds of meaning, that are related to ritual or yajna and karma in meaning action. The second about Bhakti Yoga Marga that is to respectful greeting of God in bring into reality of abstract and resfectful greeting of God in contrete. For example we use nyasa or pratima have the shape statue or mantra. The third about Jnana Marga Yoga that is the way of purified knowledge to go in direction of God. There are two kinds of knowledge. They are jnana (knowledge) and wijnana (everything is know in the knowledge). And the fourth, Raja Marga Yoga that is teach about manner or way of Yoga or medition (th mind concentration) to go in the direction of the God or Ida Sang Hyang Widhi Wasa.